Resource Endowment of Rural Areas: Indicators, Assessment Procedures - KUSSAIYNOV, Talgat; TOKENOVA, Sandugash (Journal of Environmental Management and Tourism, 2022)
T he specific objectives of the baseline study are to (a) characterize the livelihoods of rural communities with respect to their physical, natural, financial, human, and social assets, (b) identify opportunities and key constraints to productivity and resource management, and (b) establish baseline information that could be used for the monitoring, evaluation and impact assessment of socio-economic projects in the region. A structured questionnaire was used to obtain data through a number of visits. Around 1200 households were interviewed. It is established that there are significant imbalances in the distribution of economic resources among households. This circumstance objectively hinders the growth of the solvent potential of the rural population and hinders the economic development of rural areas. In addition, there are no organized forms of economic interaction of households in the studied region. Meanwhile, social capital in the form of a cooperative or other form of association is, in principle, a powerful means of solving socio-economic problems in rural areas, including in the supply of resources and the promotion of their own products on the market. The results obtained highlight the major constraints and opportunities that would guide intervention projects to improve food security and reduce poverty in the survey sites.